Studi Kemampuan Pati Biji Durian Sebagai Bahan Pengikat Dalam Tablet Ketoprofen Secara Granulasi Basah - Jufri, Mahdi; Dewi, Rosmala; Firli, Akhmad Ridwan (UI Scholars Hub, 2006)
Many type of starch from various plants can be exploited as an alternative for additional materials in tablet formulation. One of the source that have been developed as a pharmaceutical excipient is durian seed starch, which relatively easy to find in tropic area such as Indonesia. The objective of this research was to observe the ability of durio seed starch as binder in wet granulation of ketoprofen tablet formulation. Durio seed starch obtained by extraction and drying methode. Starch as a paste used in wet granulation as a binder. Tablet made by wet granulation with ketoprofen (25%) as a drug model; calcium phosphate dihidrate as a diluent; AvicelÂ® PH 102 as a disintegrant; magnesium stearat (1%) and talc (2%) as a lubricant. Placebo formula with various durio seed starch concentration (5%, 6%, 8%, 10%) in tablet compared to other binder that is cassava starch. Placebo tablet formula with better hardness and friability used in ketoprofen tablet formula and compared to cassava starch as a binder with the same concentration. Formula with durio seed starch as binder have smaller hardness and more friable than cassava starch as a binder. Thereby tablet with durio seed starch as binder have faster disintegration time than tablet with cassava starch as a binder. The dissolution test for both ketoprofen formula did not meet the pharmacopeial requirements.